The Effect of Seed Coating with Trichoderma sp. and Application of Bokashi Fertilizer to the Quality of Soybean (Glycine max. L) Seed - Sarah Sakinah Umadi; Sumadi Sumadi; Denny Sobardini Sobarna (Jurnal Biodjati, 2018)
The decrease of soybean productivity was caused by low quality of seed. To improve the quality of seed, soybean seed were coated  with Trichoderma sp. and adding bokashi organic fertilizer. This research aimed at finding the best dose combination of Trichoderma sp.  and bokashi fertilizer to improve the quality of soybeans. The research was conducted in the experiment field and Laboratory of Seed Technology at Padjadjaran University in April - August 2017. The experimental design in this research was Randomized Block Design (RBD). The treatments were the combination  of four dose values of coating the seed by Trichoderma sp. (0g/100 seeds, 1g/100 seeds, 2g/100 seeds, and 3g/100 seeds) and three dose  of bokashi (0g/polybag, 300g/polybag, and 600g/polybag) and each treatment was replicated three times. The experiment result showed that all treatments on soybean seeds did not affect the germination percentange, vigor index, and conductivity value, but affected the seed quantityof 600g/polybag of bokashi and without seed coating with Trichoderma sp.  on 100 seed mass and seed weight per plant.